Polo Kinase Interacts with RacGAP50C and Is Required to Localize the Cytokinesis Initiation Complex - Ebrahimi, Saman (American Society for Biochemistry and Molecular Biology, 2010)
The assembly and constriction of an actomyosin contractile ring in cytokinesis is dependent on the activation of Rho at the equatorial cortex by a complex, here termed the cytokinesis initiation complex, between a microtubule-associated kinesin-like protein (KLP), a member of the RacGAP family, and the RhoGEF Pebble. Recently, the activity of the mammalian Polo kinase ortholog Plk1 has been implicated in the formation of this complex. We show here that Polo kinase interacts directly with the cytokinesis initiation complex by binding RacGAP50C. We find that a new domain of Polo kinase, termed the intermediate domain, interacts directly with RacGAP50C and that Polo kinase is essential for localization of the KLP-RacGAP centralspindlin complex to the cell equator and spindle midzone. In the absence of Polo kinase, RacGAP50C and Pav-KLP fail to localize normally, instead decorating microtubules along their length. Our results indicate that Polo kinase directly binds the conserved cytokinesis initiation complex and is required to trigger centralspindlin localization as a first step in cytokinesis.